19
$\begingroup$

I need to compute the derivative of $$z=x^{x^x}$$

I made it like this:

$$y=x^x$$ so $$z=y^x$$ then $$\ln(z)=x\ln(y)$$ taking derivative from both sides: $$\frac{z'}{z}=\ln(y)+x\left(\frac{1}{y}\right)y'$$ I know that $$(x^x)'=x^x(1+\ln(x))$$ So : $$z'=z*(\ln(x^x)+x*\left(\frac{1}{x^x}\right)*(x^x)'))=x^{x^x}(x\ln(x)+x\ln(x)+x)=x^{x^x}\left(2x\ln(x)+x\right)$$ I know I did something wrong. Where is my Mistake??

Thanks alot!

$\endgroup$
  • 7
    $\begingroup$ $\ln(z)=y\ln x$ not $\ln(z)\neq x\ln y$ $\endgroup$ – kingW3 Feb 12 '17 at 21:21
  • $\begingroup$ This is a nice one with the multivariate chain rule $\endgroup$ – Omnomnomnom Feb 12 '17 at 21:22
  • $\begingroup$ Ok Ive edited $$z=y^x$$ => $$ln(z)=xln(y)$$ $\endgroup$ – Alexander Benusovich Feb 12 '17 at 21:33
  • 1
    $\begingroup$ A key error, which Daniel Nieuwerf points out in his answer, but which may not be clear is that if $y = x^x$, then $z = x^y \ne y ^x$. Indeed $y^x = (x^x)^x = x^{x\cdot x} = x^{(x^2)}$.Not the same thing at all, except when $x = 2$ (or $1$ or $0$, but for other reasons).. $\endgroup$ – Paul Sinclair Feb 13 '17 at 2:19
22
$\begingroup$

What if you represented your function as

$f(x) = x^{x^x} = \exp(x^x \cdot \ln x) = \exp(\,\exp(x\ln(x)) \cdot \ln x \, )$

Then you can apply the chain rule with the product rule.

| cite | improve this answer | |
$\endgroup$
  • 4
    $\begingroup$ Definitely how you should do it. $\endgroup$ – Simply Beautiful Art Feb 12 '17 at 22:53
15
$\begingroup$

It's $z=x^y$ not $z = y^x$ so $z= y\ln x$ not $z = x\ln y$

| cite | improve this answer | |
$\endgroup$
13
$\begingroup$

Here is the fancy way you would do it with multi-variate chain rule:

Let

$u=x\\v=x\\w=x\\y=u^v\\z=w^y$

We then have

$$\begin{align}\frac d{dx}z&=\frac{\partial z}{\partial w}\frac{dw}{dx}+\frac{\partial z}{\partial y}\frac{dy}{dx}\\&=yw^{y-1}+\ln(w)w^y\left(\frac{\partial y}{\partial u}\frac{du}{dx}+\frac{\partial y}{\partial v}\frac{dv}{dx}\right)\\&=x^x+\ln(x)x^x\left(vu^{v-1}+\ln(u)u^v\right)\\&=x^x+x^{2x}\ln(x)(1+\ln(x))\end{align}$$

| cite | improve this answer | |
$\endgroup$
7
$\begingroup$

I think your confusion stems from what you think $x^{x^x}$ means.

$x^{x^x}$ means taking $x$ to the power of $x^x$ which is distinctly different from taking $x^x$ to the power of $x$.

As an example, $3^{3^3} = 3^{(3^3)} = 3^{27}$.

$3^{3^3} \neq (3^3)^3=27^3$.

So $z \neq y^x$. Instead, $z = x^y$.

| cite | improve this answer | |
$\endgroup$
5
$\begingroup$

Your only mistake is that $x^{x^x}=x^{(x^x)}\ne (x^x)^x=x^{x^2}$.

As to the derivative, it's simply the chain rule and product rule. First let's do

$$\frac{dx^x}{dx} = \frac{de^{x\ln x}}{dx} = x^x \left(x \frac{d\ln x}{dx} + \ln x\right) = x^x(1 + \ln x).$$

Then we can do the rest:

$$\frac{d x^{x^x}}{dx} = \frac{de^{x^x\ln x}}{dx} = x^{x^x}\left(x^x \frac{d\ln x}{dx} + \ln x \frac{d x^x}{dx}\right) = x^{x^x} \left[x^{x-1} + x^x(\ln x+\ln^2 x)\right].$$

| cite | improve this answer | |
$\endgroup$
3
$\begingroup$

Here is how I did it:

$f(x)=x^{x^x}$

$\ln f(x)=x^x\ln x$

$\ln \ln f(x)=\ln{x^x \ln x}=x\ln x+\ln \ln x$

Now I derive both sides:

$\frac{(\ln f(x))'}{\ln f(x)}=\ln x +1+\frac{(\ln x)'}{\ln x}$

using the fact that $(\ln f(x))'=\frac{f'(x)}{f(x)}$, we get:

$\frac{\frac{f'(x)}{f(x)}}{\ln f(x)}=\ln x +1 +\frac{1}{x\ln x}$, and equivalently:

$\frac{f'(x)}{f(x)\ln f(x)}=\ln x +1 +\frac{1}{x\ln x}$. Multiplying by $f(x)\ln f(x)$ both sides and using the fact that $f(x)=x^{x^x}$, we get that:

$f'(x)=x^{x^x}\ln x^{x^x}(\ln x+1+\frac{1}{x\ln x})=x^x x^{x^x}\ln x(\ln x +1 + \frac{1}{x\ln x})$. Taking $x\ln x$ into the parentheses gives

$f'(x)=x^{x-1}x^{x^x}(x\ln x +x\ln^2 x+1)=x^{x^x+x-1}(x\ln x +x\ln^2 x+1)$

| cite | improve this answer | |
$\endgroup$
2
$\begingroup$

Let us first establish the derivative of $x^{f(x)}$ in general.

$$\left(x^{f(x)}\right)'=\left(e^{\ln x f(x)}\right)'=\left(\frac{f(x)}x+\ln x f'(x)\right)x^{f(x)}.$$

Then

$$(x^x)'=\color{blue}{\left(1+\ln x\right)x^{x}}$$

and

$$\left(x^{x^x}\right)'=\left(\frac{x^x}x+\ln x \color{blue}{\left(1+\ln x\right)x^{x}}\right)x^{{x^x}}=\color{green}{\left(\frac1x+\ln x+\ln^2x\right)x^xx^{x^x}}.$$


While we are at it:

$$\left(x^{x^{x^x}}\right)'=\left(\frac{x^{x^x}}x+\ln x \color{green}{\left(\frac1x+\ln x+\ln^2x\right)x^xx^{x^x}}\right)x^{x^{x^x}}.$$

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.